Longer relative telomere length in blood from women with sporadic and familial breast cancer compared with healthy controls - Gramatges, Maria M; Telli, Melinda L; Balise, Raymond; Ford, James M (Cancer epidemiology, biomarkers & prevention, 2010)
Telomeres cap the ends of chromosomes and are composed of a series of noncoding hexamer repeats. Telomeres protect the integrity of DNA coding sequences and are integral to the maintenance of genomic stability. Previous studies have shown an association between shortened lymphocyte telomeres and increased risk for specific cancers. However, the association between telomere length and breast cancer risk is less clear. We examined the relative telomere length (RTL) in blood from women with no personal or family history of cancer (controls) compared with different populations of women with breast cancer and women at high genetic risk for developing breast cancer. RTL was determined as the telomere to single gene copy number ratio assessed by quantitative PCR. Breast cancer cases (low risk, n = 40; high risk, n = 62) had significantly longer RTL compared with unaffected controls (n = 50; mean RTL = 1.11 versus 0.84; P < 0.0001). The assessment of risk by RTL quartile showed an increased risk for breast cancer with each longer quartile, with the most significant risk observed in the longest quartile (odds ratio, 23.3; confidence interval, 4.4-122.3; P < 0.0003). Women without breast cancer but at high risk due to family history (n = 30) also showed longer telomeres than controls (mean RTL = 1.09 versus 0.84; P < 0.0001). Our analysis supports previous findings of longer RTL in breast cancer cases compared with controls, and is the first to observe longer RTL in women without breast cancer identified as high risk based on family history.